Scaling up of Climate-Smart Villages across the 38 districts of Bihar - CGIAR Research Program on Climate Change, Agriculture and Food Security; International Maize and Wheat Improvement Center (2016)
Bihar’s agricultural production is regularly affected by droughts and floods. The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and International Maize and Wheat Improvement Center (CIMMYT) showcased climate-smart agriculture (CSA) practices to high-level government officials in several Climate-Smart Villages (CSV). After the visit, the government of Bihar decided to implement CSA and CSVs in all districts of Bihar. On-farm evidence from the CSVs and events organized by CIMMYT and partners inspired these government policies. They are expected to positively influence the ability of hundreds of thousands small-holder farmers in Bihar to improve their nutrition and livelihoods while coping with the droughts and floods.